The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1590/s0074-02761993000400005
|View full text |Cite
|
Sign up to set email alerts
|

Difference in susceptibility to lysis between clones of the Y strain of Trypanosoma cruzi

Abstract: Three clones isolated from the Y strain of Trypanosoma cruzi--YP1, YP2 and YP3--were adapted to in vitro cultivation in VERO cells. The recovery of the parasites from the Y strain and clone YP3 was similar after 24 hr of contact with cells (3.2% and 2.7%, respectively) and much lower than the recovery of clones YP1 and YP2 (56.7% and 60.0% of inoculum, respectively). After five days incubation, the ratio Trypomastigotes/Amastigotes released into the supernatants was about 90/10 for clone YP1, YP3 and Y strain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been shown that the susceptibility of T. cruzi to lysis by complement varies according to the strain [32]; complement lysis assays showed that the Colombian T. cruzi strain is more susceptible to lysis than the Y T. cruzi strain at all serum concentrations [33]. Indeed, even within the same strain, variations in susceptibility have been observed among different clones [34]. There are no reports of T. cruzi lysis by complement with Ninoa strain; in our study the results showed a high percentage of lysis, similar to other Mexican Trypanosoma cruzi isolates reported by other authors [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the susceptibility of T. cruzi to lysis by complement varies according to the strain [32]; complement lysis assays showed that the Colombian T. cruzi strain is more susceptible to lysis than the Y T. cruzi strain at all serum concentrations [33]. Indeed, even within the same strain, variations in susceptibility have been observed among different clones [34]. There are no reports of T. cruzi lysis by complement with Ninoa strain; in our study the results showed a high percentage of lysis, similar to other Mexican Trypanosoma cruzi isolates reported by other authors [32].…”
Section: Discussionmentioning
confidence: 99%
“…The Y strain of T. cruzi was used for all experiments. Trypomastigote forms were cultured and purified from monkey kidney epithelial cell line VERO, as previously described (Braga et al, 1993). Parasites were harvested after 6 days in culture, centrifuged at 150×g for 10 min at room temperature, counted in a Neubauer chamber, centrifuged at 450×g for 10 min at 4°C, suspended in 10% FBS supplemented 199 medium and used for infection of cultures and co-cultures.…”
Section: Parasitesmentioning
confidence: 99%
“…The T. cruzi strains DM28c ( T. cruzi I type) and Y ( T. cruzi II type) were used in infection experiments (Zingales, 2018 ). Trypomastigote forms were cultured and purified using kidney epithelial lineage (VERO) cells, as described previously (Braga et al, 1993 ). After 6 days of culture, the parasites collected were centrifuged at 150 G for 10 min at room temperature and counted in a Neubauer chamber, centrifuged at 450 G for 10 min at 4°C and suspended 90% DMEM medium in 10% fetal calf serum (FCS) and added to cultures.…”
Section: Methodsmentioning
confidence: 99%